GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TERHADAP PERTOLONGAN PERTAMA PADA KECELAKAAN LALU LINTAS DI BANJAR BUAGAN, DESA PEMECUTAN KELOD: DESCRIPTION OF THE PUBLIC LEVEL OF KNOWLEDGE OF FIRST AID IN TRAFFIC ACCIDENTS IN BANJAR BUAGAN, PEMECUTAN KELOD - Asdiwinata, I Nyoman; Yundari, A.A Istri Dalem Hana; Widnyana, I Putu Angga (Bali Medika Jurnal, 2019)
Traffic accidents cause various injuries to death. In addition to the accident victims who died directly at the scene, the first aid factor for accident victims is very important for accident victims to prevent more severe trauma. The purpose of this study was describe the level of knowledge of the community on first aid in traffic accidents in Banjar Buagan, Pemecutan Kelod. This research was a descriptive study with a cross sectional approach. The sample of this studied was 198 respondents used non probability sampling with purposive sampling technique. Data was collected by questionnaire sheets on the level of community knowledge of first aid in traffic accidents with the results of the validity test r count>0.312 and reliability test 0.931>0.750. The data were analyzed by the SPSS program used univariate analysis. The results of this study show that the majority of people aged 36-45 years old, male sex, high school / vocational education, private employment. The community's knowledge of first aid in traffic accidents was found to have a high level of knowledge, namely 125 respondents (63.1%). It was recommended for health workers to provide adequate information to the public about how to do first aid in traffic accidents through counseling.